Health Related Quality of Life of Cancer Patients in Ethiopia. (15th April 2018) - Abegaz, Tadesse Melaku; Ayele, Asnakew Achaw; Gebresillassie, Begashaw Melaku
Abstract : Background. Neoplasm, AKA cancer (Ca), is associated with major morbidity and mortality. Aim. Measurement of health related quality of life (HRQoL) of Ca patients is uncommon in Ethiopia. The present study determined the HRQoL and its determinants among people living with Ca in north Ethiopia. Methods. A prospective hospital based study was conducted from 1 January 2017 to 30 August 2017 on Ca patients attending cancer treatment center of University of Gondar Teaching Hospital. The European Organization for Research and Treatment of Cancer Questionnaire version 3 was utilized to collect the data. The rate of QoL was presented using means with standard deviation (±SD). Binary logistic regression was employed to determine factors associated with HRQoL. Result. The present study is based on the findings from 150 subjects. The rate of QoL was 52.7 (20.1) (mean ± SD). The highest functional status was emotional functioning 61 (25.5). Patients with no disease metastasis, 92.1 (5.1), had high QoL as compared to metastasis, 22.1 (18.9)( p = 0.03 ) . Patients with affected physical functioning have a 20% reduction in QoL and Adjusted Odds Ratio (AOR) of 0.794 [0.299–891]. Patients with low satisfaction level with the provided care, 0.82 [0.76–0.93], and those with unmet needs, 0.85 [0.80–0.95], experienced reduced level of HRQoL. Conclusion. Health related quality of life of cancer patients was found to be low in Ethiopia. Patients with limited rate of disease metastasis had improved HRQoL. Further, the unmet needs of Ca patients and the level of satisfaction with the overall care were found to influence the extent of HRQoL. Therefore, early detection of neoplasm to arrest metastasis is warranted in order to achieve better QoL. In addition, addressing the unmet needs of these patients and ensuring higher satisfaction rate are recommended to maintain adequate HRQoL.